KOMPARASI FUZZY AHP, TOPSIS DAN SMART UNTUK PEMILIHAN SUPPLIER - Samdan Wibawa; AD Ekawati; Budian Maryadi; Nurafni Fitriyani; AANP Redi (Jurnal Manajemen Industri dan Logistik, 2021)
abstractPT.XYZ is a manufacturing drilling tools company where the assembly parts are supplied by the other companies. With 4% average percentage of not good (NG) from incoming assembly inspections in 2019 and the peak of 9,8% in April, the company needs to review its current suppliers. This research compares the result of the supplier selection using FAHP, TOPSIS and SMART methods to get the recommended suppliers. The three methods resulted the same suppliers with the highest value which is Supplier#3 and the three lowest values which are Supplier#4, Supplier#7 and Supplier#2 it is recommended to re-evaluation to improve their performance. This research compares the result of the supplier selection using FAHP, TOPSIS and SMART methods to get the recommended suppliers. The questionnaires were given to 12 subject matter experts. Using FAHP, TOPSIS and SMART methods to get the recommended suppliers..